Study on Solvent Extraction of Mercury Complex With DB18C6 - Alkubaisy, R.K.; Almureb, S.R.; Alhaideri, A.M.; Radhi, S.W. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Mercury(II) ion is extracted as ion pair with thiocyanate using DCM .The effects of different parameters affecting the ease of extraction are determined . These parameters are  pH ,Thiocyanate ion concentration ,type and concentration of the counter cation concentration of the reagent , temperature and type of solvents .Other crown ethers (15C5 DB24C , DCH18C6 and  18C6 and cryptand- 222 are investigated as extracting reagents  using slop analysis method UV-visible and IR spectrometry .CHN analysis and melting points determination  are perfored for comlex analysis .All these investigations indicated the formula [k+CE]2[Hg (SCN )4]-2.